2011
DOI: 10.1080/00071668.2011.640929
|View full text |Cite
|
Sign up to set email alerts
|

Rice bran lysolecithin as a source of energy in broiler chicken diet

Abstract: 1. Rice bran lysolecithin (RBL) was evaluated in broiler chicken diets. In the first experiment, RBL was included in diet at 0, 0·5, 2, 8 and 32 g/kg and fed to 250 broiler chickens from 0 to 42 d of age. In the second experiment, RBL was fed at 0, 25 and 50 g/kg diet to 405 day-old broiler chickens until 21 d of age, while during the finisher phase (22-35 d of age) chickens receiving each concentration of RBL were given all three concentrations of RBL in a 3 × 3 factorial manner. The diets were isocaloric. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 16 publications
3
10
1
2
Order By: Relevance
“…However, the data of the present study are not in agreement with those of Raju et al (2011) and Boontiam et al (2016), who observed an increase in pancreatic weight when birds were fed with exogenous emulsifier, and the increase in relative body weight, according to the authors, might be indicative of increased digestion and lipid absorption.…”
Section: Concomitantcontrasting
confidence: 99%
“…However, the data of the present study are not in agreement with those of Raju et al (2011) and Boontiam et al (2016), who observed an increase in pancreatic weight when birds were fed with exogenous emulsifier, and the increase in relative body weight, according to the authors, might be indicative of increased digestion and lipid absorption.…”
Section: Concomitantcontrasting
confidence: 99%
“…Due to a higher demand for energy in the final stages, the lysophospholipids presence was effective in increasing broiler BW gain independent of the inclusion of S or T. Zhang et al (2011) found higher values of apparent metabolisable energy (AME) in diets with lysophospholipids only after 35 d, confirming the greatest pronouncement of lysophospholipids on energy demand in the final phase. Furthermore, the lysophospholipids derived from rice bran was recommended as a source of energy for broilers with beneficial effects on performance and fat digestibility (Raju et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, dietary LPL improves the digestion of fats and oils. Some researchers showed that LPL prepared from rice bran and soybean increased the digestibility of fats and fatty acids (FA) in broilers (Jansen, Nuyens, Buyse, Leleu, & Van Campenhout, ; Raju et al., ). In addition to being a highly efficient food emulsifier, LPL acts as a lipid‐mediator in various physiological functions.…”
Section: Introductionmentioning
confidence: 99%